Utilization of Weak Artificial Intelligence for Interactive Learning - Zikri, Abdal; Hari Anna Lastya (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2026)
The use of artificial intelligence technology can be realized in various aspects, including in the learning process that implements weak artificial intelligence (gamma.app) as a newer, innovative and creative learning medium. This study aims to explore the use of gamma.app in creating a more interactive and effective learning experience in schools and to determine students' responses to AI. This study uses a quantitative approach with an experimental method with pre-test sheets, post-test sheets, and questionnaire sheets as research instruments. The experiment was conducted by utilizing weak artificial intelligence (gamma.app) during the learning process. This study shows that gamma.app can help teachers and students in creating interesting and communicative presentations, as well as increasing student engagement in the learning process. This is evident from the results of the pre-test and post-test sheets that there is a significant difference in the average score, namely pre-test 44.1% and post-test 65.1% as well as the achievement of learning objectives. The use of gamma.app can foster student activeness and creativity during learning. The results of student responses show that 93.5% strongly agree with the use of weak artificial intelligence for interactive learning